Domain glass (Phys. Status Solidi B 10/2014). Issue 10 (October 2014) - Salje, E. K. H.; Ding, X.; Aktas, O.
<x xml:space="preserve">Abstract</x> Non‐ergodic, glass‐like structures are commonly observed whenever the degree of disorder in a structural phase transition is large. Salje, Ding and Aktas (on pp. 2061–2066) show that such disorder can be generated by nanostructures when dense domain patterns are formed. Domain glasses are characterized by massive elastic softening compared with the homogeneous matrix. Domain glasses show typical Vogel–Fulcher statistics under external forcing when the domain pattern is changed while the underlying matrix remains fully crystalline without any defects or other structural disorder. A typical domain glass is the dynamic tweed structure of interwoven elastic waves which shift and fluctuate inside the matrix with great ease. The cover images show a typical induced twin domain pattern (main image) and the structure factor of a dense, glassy pattern of intersecting twin wall (inset). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>